2020
DOI: 10.3389/fmicb.2020.00607
|View full text |Cite
|
Sign up to set email alerts
|

Urease Expression in Pathogenic Yersinia enterocolitica Strains of Bio-Serotypes 2/O:9 and 1B/O:8 Is Differentially Regulated by the OmpR Regulator

Abstract: Yersinia enterocolitica exhibits a dual lifestyle, existing as both a saprophyte and a pathogen colonizing different niches within a host organism. OmpR has been recognized as a regulator that controls the expression of genes involved in many different cellular processes and the virulence of pathogenic bacteria. Here, we have examined the influence of OmpR and varying temperature (26 • C vs. 37 • C) on the cytoplasmic proteome of Y. enterocolitica Ye9N (bio-serotype 2/O:9, low pathogenicity). Differential labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…OmpR has been identified as a transcriptional regulator of various genes involved in the control of diverse cellular processes and functions in bacteria including Y. enterocolitica [ 58 , 68 , 75 , 87 , 88 ]. Based on the results of proteomic analyses, the production of a number of membrane proteins involved in the uptake and transport of compounds into Y. enterocolitica cells, including several that participate in iron or heme acquisition, is subject to control by the regulator OmpR [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…OmpR has been identified as a transcriptional regulator of various genes involved in the control of diverse cellular processes and functions in bacteria including Y. enterocolitica [ 58 , 68 , 75 , 87 , 88 ]. Based on the results of proteomic analyses, the production of a number of membrane proteins involved in the uptake and transport of compounds into Y. enterocolitica cells, including several that participate in iron or heme acquisition, is subject to control by the regulator OmpR [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding region of the OmpR was identified as 5′CATTTATTTACATTTAC3′ (Figure 3) by a DNase I footprinting assay. The binding sequence showed 45% identity to the E. coli consensus sequence (5′TTTTACTT TTGTAACATAT3′; Maeda et al, 1991) and 55% identity to that of Y. enterocolitica (5′ATTTATTGATGGTAACAATT3′; Nieckarz et al, 2020). Many two-component systems regulating proteins can autoregulate their own expression by binding to their promoters, and this kind of feedback allows the regulatory functions of the system to be more flexible (Groisman, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research studies reported that urease as a virulence factor of various pathogenic bacteria is related to the progress of several long-lasting diseases, including colitis, atherosclerosis, and rheumatoid arthritis [ 33 , 35 ]. Similarly, assimilatory ferredoxin-dependent nitrate reductase (nirA) is essential for the full virulence of various bacteria [ 36 , 37 ]. In the light of our results, three distinct subunits with alpha, beta, and gamma (as a crucial structural component of urease [ 35 , 36 ]) and nirA were enriched in AF patients with high thromboembolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, assimilatory ferredoxin-dependent nitrate reductase (nirA) is essential for the full virulence of various bacteria [ 36 , 37 ]. In the light of our results, three distinct subunits with alpha, beta, and gamma (as a crucial structural component of urease [ 35 , 36 ]) and nirA were enriched in AF patients with high thromboembolic risk. Several studies demonstrated that 4-methylcatechol, a flavonoid metabolite formed by GM, with potent vasorelaxant, anti-inflammatory, antidiabetic, and antiplatelet effects, reduces endothelial dysfunction [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%